FROM VIRAL TO TRUST: PERAN BRAND TRUST DALAM MEMEDIASI PENGARUH VIRAL MARKETING, INFLUENCER MARKETING, DAN ONLINE CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PRODUK GLAD2GLOW DI TIKTOK SHOP - Safira Khoirotunnisa; Edita Rachma Kamilah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of viral marketing, influencer marketing, and online customer review on purchase intention with brand trust as a mediating variable for Glad2Glow skincare products on TikTok Shop. This research employed a quantitative method using purposive sampling techniques involving 180 respondents who are active TikTok users and follow the official Glad2Glow account. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS 4.0 software. The results indicate that viral marketing, influencer marketing, and online customer review have a positive and significant effect on brand trust, while influencer marketing and brand trust also have a positive and significant effect on purchase intention. However, viral marketing and online customer review do not have a direct significant effect on purchase intention. In addition, brand trust is proven to mediate the influence of viral marketing, influencer marketing, and online customer review on purchase intention for Glad2Glow products on TikTok Shop. These findings indicate that the success of digital marketing is not only determined by the wide reach of content on social media, but also by the company’s ability to build and maintain consumer trust in the brand.